Hubungan Tingkat Spiritualitas dengan Tingkat Stres Paska Bencana Banjir - Gati, Norman Wijaya; Kusumadewi, Berlian Nurtyashesti; Waluyo; Arifin, Zaenal (STIKES Ngesti Waluyo, 2024)
The Semanggi sub-district, located in Surakarta, is an area that is often affected by flooding during the rainy season. This flood condition will cause physical and psychological impacts. The physical impacts of flooding include loss of life and damage to infrastructure, while the psychological impacts include anxiety disorders, stress, and post-traumatic syndrome. Flood disasters cannot be predicted, so these conditions often require survivors to adapt physically and psychologically. When a disaster occurs, it stimulates the brain to form a perception of the severity of the stress. Being resilient when facing stress requires internal and external support, trust in the Creator, and social support. This research aims to determine the relationship between the level of spirituality and stress in post-flood disaster survivors. This type of research uses a cross-sectional quantitative approach. This research was conducted in March-May 2023 in the Semanggi sub-district, RW 10-13, which was affected by the flood. The population in this study was 1480 heads of families in RW 10-13, Semanggi sub-district. The numbers of samples were determined using the Slovin formula, consisting of 94 respondents who were selected based on the inclusion and exclusion criteria. Stress levels were measured using The Perceived Stress Scale-10, and spirituality level was measured using Daily Spiritual Experience scale. Based on the Spearman'rho correlation analysis test, the result was 0.664. There is no relationship between stress levels and spirituality levels.